2016
DOI: 10.1002/crq.21167
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Helpful Tensions between Divorce Mediators and Clients: A Relational Dialectical Analysis

Abstract: Addressing calls for more mediation process research, this qualitative study explored which contradictory tensions are in play in a helpful working relationship between mediators and their clients. Data were collected in semistructured interviews with divorce mediators ( n = 12). Relational dialectical analysis detailed how divorce mediators varied practice styles along the central opposing pulls of client self-determination and professional control, neutrality and engagement, and effi ciency and exploration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…An important element in this approach seemed to be the mediators' ability to keep the attention on these conflict‐driving topics without losing sight of the agreement about the children's daily care. The findings here are in accordance with some of those highlighted by Baitar et al ().…”
Section: Some Central Strategies In the Face Of Custody Conflictssupporting
confidence: 94%
See 1 more Smart Citation
“…An important element in this approach seemed to be the mediators' ability to keep the attention on these conflict‐driving topics without losing sight of the agreement about the children's daily care. The findings here are in accordance with some of those highlighted by Baitar et al ().…”
Section: Some Central Strategies In the Face Of Custody Conflictssupporting
confidence: 94%
“…However, the purposes mostly underlined have been to help the parties talk about their emotional reactions, obtain a clearer meaning of what they might express, and explore if and in what way such reactions may inhibit the parents in the process of finding solutions (Emery & Sbarra, 2005;Poitras & Raines, 2013;Saposnek, 2004). A recent interview study about how mediators handled tensions between themselves and clients presents topics close to those we will address here (Baitar, De Mol, & Rober, 2016).…”
Section: Mediation As An Intervention For Divorcing or Separating Pmentioning
confidence: 98%
“…If the socioemotional needs of clients are addressed, they can communicate their concerns clearly and calmly so that mediators can examine their underlying agenda and functional goals. Clients found this process very helpful and valued it even more than efficiency, expediency, or finality of resolution (Baitar, De Mol, & Rober, ). Nevertheless, mediators should avoid actively making room for clients' emotions, as doing so might hamper the settlement attempt.…”
Section: Literature Reviewmentioning
confidence: 99%
“…She demonstrated how both mediators and parties switch between these discourses "when one seems unproductive or leads to trouble" (4), but she found that the moral discourse predominated in US mediation settings. Baitar, de Mol, and Rober ( 2016 ) argued that we should take a relational approach and acknowledge the interplay of complex and contradictory processes that may occur during mediation. An investigation of some of the complex and contradictory aspects within the mediation dynamic may off er insights to mediators and training organizations.…”
Section: Features Of Mediation Talkmentioning
confidence: 99%
“…Th e distinct, and not always compatible, agendas in multiparty interaction can also be viewed as a problem of the multipurpose nature of the mediation process. We saw how mediators may shift strategically among moral, legal, and therapeutic discourses (Merry 1990 ) or shift between pragmatic and emotional positions (Baitar et al 2016 ) as a way of managing confl ict and disagreement in the sessions (e.g., in Figure 4 ), but because these diff erent discourses have specifi c moral orders, this may distract parties from the progression of the mediation goal. Th erapeutic discourse may seem appropriate in the context of parties' orientation but may mean that mediators attend to parties' concerns at the cost of the other party or of the mediation outcome.…”
Section: Multiple Agendas and Discourses As A Characteristic Of The Mmentioning
confidence: 99%